Fintech as Accelerating Factor of Inclusive, Sustainable Development - A. V. Lopukhin; E. A. Plaksenkov; S. N. Silvestrov (Мир новой экономики)
This article focuses on the impact of the financial sector on inclusive, sustainable development. The paper aims to study the impact of the fintech industry and financial inclusion on the development of the financial system to achieve the UN SDGs. We discussed various approaches to the content of the “fintech” and “ecosystem” terms and offered an interpretation of the term “financial inclusion”. We used comparative and system analysis methods to study the publications of many authors who found that a developed and inclusive financial system affects the reduction of poverty and inequality, welfare and employment, consumer market, economic growth, sustainable development, etc. At the same time, we showed variants of the relationship between increased access to financial services and financial stability, which can both be positive and negative. The state of the financial services market in Russia, which ranks high in various ratings in terms of financial inclusion, is described in detail. Further, we considered the barriers to the growth of financial inclusion in Russia and ways to overcome them. The practical significance of the work lies in the possibility of its use in the development of key areas of financial market development. Next, more attention needs to be paid to regulatory influences on consumer behaviour in selecting services and their providers.